A New Species in Pseudophialophora From Wild Rice and Beneficial Potential - Zhu, Jia-Nan; Yu, Yi-Jun; Dai, Meng-Di; Zeng, Yu-Lan; Lu, Xuan-Jun; Wang, Ling; Liu, Xiao-Hong; Su, Zhen-Zhu; Lin, Fu-Cheng (Frontiers in Microbiology, 2022)
Wild rice (Oryza granulata) is a natural resource pool containing abundant unknown endophytic fungi species. There are few reports on the endophytic fungi in wild rice. Here, one isolate recovered from wild rice roots was identified as a new species Pseudophialophora oryzae sp. nov based on the molecular phylogeny and morphological characteristics. Fluorescent protein-expressing P. oryzae was used to monitor the fungal colonization pattern. Hyphae invaded the epidermis to the inner cortex but not into the root stele. The inoculation of P. oryzae promoted the rice growth, with the growth parameters of chlorophyll content, shoot height, root height, fresh shoot weight, fresh root weight and dry weight increasing by 24.10%, 35.32%, 19.35%, 90.00%, 33.3% and 79.17%, respectively. P. oryzae induced up-regulation of nitrate transporter OsPTR9 and potassium transporter OsHAK16 by 7.28 ± 0.84 and 2.57 ± 0.80 folds, promoting nitrogen and potassium elements absorption. In addition, P. oryzae also conferred a systemic resistance against rice blast, showing a 72.65% and 75.63% control rate in sterile plates and potting conditions. This systemic resistance was mediated by the strongly up-regulated expression of resistance-related genes NAC, OsSAUR2, OsWRKY71, EL5 and PR1α. Since P. oryzae can promote rice growth, biomass and induce systemic disease resistance, it can be further developed as a new biogenic agent for agricultural production, providing a new approach for biocontrol of rice blast.